2015
DOI: 10.1164/rccm.201410-1875oc
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Exposure to Traffic Emissions and Fine Particulate Matter and Lung Function Decline in the Framingham Heart Study

Abstract: Rationale: Few studies have examined associations between longterm exposure to fine particulate matter (PM 2.5 ) and lung function decline in adults.Objectives: To determine if exposure to traffic and PM 2.5 is associated with longitudinal changes in lung function in a population-based cohort in the Northeastern United States, where pollution levels are relatively low.Methods: FEV 1 and FVC were measured up to two times between 1995 and 2011 among 6,339 participants of the Framingham Offspring or Third Genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
163
3
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 248 publications
(177 citation statements)
references
References 37 publications
10
163
3
1
Order By: Relevance
“…Although some studies have also found proportional associations of air pollution with FEV 1 and FVC in a restrictive pattern (8,13), other studies have found a largermagnitude association with FEV 1 than FVC, suggesting an obstructive effect involving the larger airways (9,30,31). Two recent studies that examined long-term PM 2.5 and BC exposure in the Boston area using the same models as the present study found restrictive patterns of effects on adult lung function and lung function decline (21,32). One possible explanation for the restrictive pattern of associations we found is that air pollution may slow lung growth in children (and accelerate lung function decline in adults).…”
Section: Discussionsupporting
confidence: 43%
“…Although some studies have also found proportional associations of air pollution with FEV 1 and FVC in a restrictive pattern (8,13), other studies have found a largermagnitude association with FEV 1 than FVC, suggesting an obstructive effect involving the larger airways (9,30,31). Two recent studies that examined long-term PM 2.5 and BC exposure in the Boston area using the same models as the present study found restrictive patterns of effects on adult lung function and lung function decline (21,32). One possible explanation for the restrictive pattern of associations we found is that air pollution may slow lung growth in children (and accelerate lung function decline in adults).…”
Section: Discussionsupporting
confidence: 43%
“…Environmental and occupational exposures are linked to the development of COPD in the general population [67][68][69][70]. In homozygous ZZ individuals, exposure to dust, gas and fumes leads to a greater decline in lung function, even in nonsmoking ZZ subjects, particularly after the age of 50 years [71,72].…”
Section: Effects Of Environmental and Occupational Exposuresmentioning
confidence: 99%
“…Длительное воздействие РМ2,5 способствует возник-новению и обострению ХОБЛ [31,32] и снижению пока-зателей функции внешнего дыхания [33][34][35]. С увеличе-нием уровня PM в атмосфере было отмечено увеличение распространенности и симптомов бронхиальной астмы (БА) [32,36].…”
Section: долговременное воздействие рмunclassified